Transcriptional precision in photoreceptor development and diseases – Lessons from 25 years of CRX research - Zheng, Yiqiao; Chen, Shiming (Frontiers in Cellular Neuroscience, 2024)
The vertebrate retina is made up of six specialized neuronal cell types and one glia that are generated from a common retinal progenitor. The development of these distinct cell types is programmed by transcription factors that regulate the expression of specific genes essential for cell fate specification and differentiation. Because of the complex nature of transcriptional regulation, understanding transcription factor functions in development and disease is challenging. Research on the Cone-rod homeobox transcription factor CRX provides an excellent model to address these challenges. In this review, we reflect on 25 years of mammalian CRX research and discuss recent progress in elucidating the distinct pathogenic mechanisms of four CRX coding variant classes. We highlight how in vitro biochemical studies of CRX protein functions facilitate understanding CRX regulatory principles in animal models. We conclude with a brief discussion of the emerging systems biology approaches that could accelerate precision medicine for CRX-linked diseases and beyond.